PSYCHOLOGICAL FACTORS OF ADAPTATION OF WOMEN AND CHILDREN IN MILITARY FAMILIES TO THE NEW SOCIAL ENVIRONMENT. (Universal International Scientific Journal, 2026)
This article examines the psychological aspects of the process of adaptation of women in military families to a new socio-environment. The main factors influencing women's adaptation, including stress and anxiety management strategies, the role of social support systems, and the effectiveness of special psychological programs, are analyzed in detail.
Keywords: military families; women's adaptation; psychological mechanisms